2012
DOI: 10.1002/ijc.27759
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of T‐cell infiltration during the course of ovarian cancer: The gradual shift from a Th17 effector cell response to a predominant infiltration by regulatory T‐cells

Abstract: The type of immune cells that are present within the tumor microenvironment can play a crucial role in the survival of patients. However, little is known about the dynamics of the tumor-infiltrating immune cells during disease progression. We studied the immune cells that infiltrated the tumor tissues of ovarian cancer patients at different stages of disease. The early stages of development of ovarian carcinomas were characterized by a strong Th17 immune response, whereas in stage II patients, recruitment of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 58 publications
1
84
1
3
Order By: Relevance
“…17 Further, Fialova et al showed a transition from a strong Th17 immune response in early cancer stages to a dominant population of Tregs by late stages in ovarian cancer patient samples, suggesting tumor progression sculpts Treg involvement in the local immune environment. 51 Even after treatment with neo-adjuvant chemotherapy, lower FOXP3CTreg infiltration is correlated with increased survival. 52 In contrast to above studies, a recent evaluation of tumor specimens from 73 ovarian cancer patients found that Treg frequency was a positive prognostic factor and no association could be made with other TILs.…”
Section: Regulatory T-cells and Survival Impact In Ovarian Cancermentioning
confidence: 99%
“…17 Further, Fialova et al showed a transition from a strong Th17 immune response in early cancer stages to a dominant population of Tregs by late stages in ovarian cancer patient samples, suggesting tumor progression sculpts Treg involvement in the local immune environment. 51 Even after treatment with neo-adjuvant chemotherapy, lower FOXP3CTreg infiltration is correlated with increased survival. 52 In contrast to above studies, a recent evaluation of tumor specimens from 73 ovarian cancer patients found that Treg frequency was a positive prognostic factor and no association could be made with other TILs.…”
Section: Regulatory T-cells and Survival Impact In Ovarian Cancermentioning
confidence: 99%
“…Tumor-infiltrating immune cells have been described in most solid tumors (3,4). The type, the density, and the location of immune cells in the tumor microenvironment, defined as immune contexture strongly affect the prognosis of cancer patients (4)(5)(6)(7). In non-small cell lung cancer (NSCLC), a high density of mature dendritic cells (DC) correlates with long-term survival of the patients (8) and with a strong infiltration by CD8 þ T cells that are predominantly of the effector-memory phenotype (9).…”
Section: Introductionmentioning
confidence: 99%
“…Fialová et al suggested that the development of antitumor immune responses in ovarian cancer patients is highly dynamic. The recruitment of Th17 cells with higher IL17 and IL21 expression levels in ovarian cancer tissues has been reported in the early stages of disease (Fialová et al 2013), and a lower level of IL17 has been reported in more advanced ovarian cancer-associated ascites (Kryczek et al 2009). The expression levels of IL17a and IL21 in Receiver operating characteristic (ROC) curves of the overall score for disease relapse (A) and disease-related death (B) of ovarian cancer patients in the derivation group (NTUH set), validation group (NCKUH set), and all patients.…”
Section: Discussionmentioning
confidence: 99%